The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2019
DOI: 10.1111/obr.12858
|View full text |Cite
|
Sign up to set email alerts
|

The influence of maternal body mass index, maternal diabetes mellitus, and maternal smoking during pregnancy on the risk of childhood‐onset type 1 diabetes mellitus in the offspring: Systematic review and meta‐analysis of observational studies

Abstract: Summary There is emerging evidence that events occurring before and shortly after birth may be important in determining the risk of childhood‐onset type 1 diabetes mellitus (T1DM). We aimed to summarize and synthesize the associations between maternal body mass index (BMI), maternal diabetes mellitus (DM), and maternal smoking during pregnancy and the risk of childhood‐onset T1DM in the offspring by performing a systematic review and meta‐analysis of observational studies. A random effects model was used to ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 113 publications
6
17
0
Order By: Relevance
“…These results involve six countries (Norway, Denmark, Sweden, UK, USA and Australia) and 9872 children with type 1 diabetes, of which 16% were exposed to prenatal smoking. Our meta-analytic estimates are consistent with a recent meta-analysis [39]. However, our results are inconsistent with the HLA-matched case-control study that reported increased type 1 diabetes risk for children exposed to prenatal smoking [13].…”
Section: Discussionsupporting
confidence: 58%
“…These results involve six countries (Norway, Denmark, Sweden, UK, USA and Australia) and 9872 children with type 1 diabetes, of which 16% were exposed to prenatal smoking. Our meta-analytic estimates are consistent with a recent meta-analysis [39]. However, our results are inconsistent with the HLA-matched case-control study that reported increased type 1 diabetes risk for children exposed to prenatal smoking [13].…”
Section: Discussionsupporting
confidence: 58%
“…Based on the results, there was a significant association between mother's GDM and childhood type 1 diabetes. Compatible to our finding, Hidayat et al, have indicated an association between maternal gestational diabetes mellitus and increased risk of childhood T1 DM (16). Kawasaki et al, also confirmed our results.…”
Section: Discussionsupporting
confidence: 89%
“…Our finding that maternal smoking seemed to protect against type 1 diabetes is interesting and has been previously reported [36]. The mechanism is still largely unknown and requires further investigation, and there is of course always the possibility that maternal smoking is merely a confounding factor.…”
Section: Discussionsupporting
confidence: 76%